Influence Simulation Model Learning to Motivation and Learning Outcomes Participant Educate Class X In English Subject - Sofwan, Sofwan; Wibowo, Sigit; Waspodo, Muktiono; Hartono, Rudi (CV Media Inti Teknologi, 2024)
The aim of the research is to determine effective learning models in English subjects to improve motivation and learning outcomes.Methods research used is experiment quantitative with design factorial two, where the variables tied up is results learning English, while variable free is motivation learning and the learning model being tested (learning model based on simulation and projects). The population of this study was all grade X students of SMA Insan Kamil Bogor, and the sample used was selected randomly using the random cluster sampling technique.Two group chosen For taught with two different learning models (learning models) based on simulation and learning models based on project). Research results show existence improvement motivation and results Study participant educate in eye English lessons after taught use second method said. Besides that, there is interaction between the learning models used with motivation and results learn English participant educate. However, no found significant difference between results Study participant students who are taught using a learning model based on project with what is taught using a learning model based on simulation. In conclusion, use an appropriate learning model with eye lesson can increase results learning and motivation participant educate, so that experience Study they become more maximum.